Morocco : The Sub-Saharan Expansion of Moroccan Banks: Challenges and Opportunities. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper presents an overview of the cross-border expansion of Moroccan banks in sub-Saharan Africa (SSA). It discusses policies to minimize possible negative spillovers and address the main supervisory challenges. It builds on the analysis and main results of a Pan-African Cross-Border Exercise-a joint initiative by the IMF's African and Monetary and Capital Markets departments, with the collaboration of the Middle East and Central Asia department. It highlights that that Morocco could play an instrumental role by providing technical assistance to other supervisors in the region, and the SSA region may benefit from the Moroccan experience of good practices in many areas and relatively advanced supervisory capacity.